P128 Sleep Need is more Strongly Associated with Self-rated Health and Daytime Function than Sleep Duration. (7th October 2021) - Scott, H; Appleton, S; Reynolds, A; Gill, T; Melaku, Y; Adams, R; Catcheside, P; Perlis, M
Abstract: Introduction: Most studies examining associations between sleep and health outcomes focus on sleep duration or efficiency, ignoring individual differences in sleep need. We investigated whether sleep need is a more influential correlate of self-rated daytime function and health than sleep duration. Methods: This study is a secondary analysis of the 2019 Sleep Health Foundation online survey of adult Australians (N=2, 044, aged 18–90 years). Hierarchical multiple linear regressions assessed variance explained by demographics (Model 1: age, sex, BMI), self-reported sleep duration (Model 2: Model 1 + weighted variable of weekday/weekend sleep duration), and individual sleep need (Model 3: Model 2+ how often they get enough sleep to feel their best the next day, on a 5-point scale) on daytime function items for fatigue, concentration, motivation, and overall self-rated health (EQ-5D, VAS 0–100). Results: Sleep need explained an additional 17.5–18.7% of the variance in fatigue, concentration, motivation, and health rating (all p < 0.001 for R² change) in Model 3. Model 2 showed that sleep duration alone only explained 2.0–4.1% of the variance in these outcomes. Findings were similar when stratified by sex. Sleep need also explained greater variance for older adults than for younger and middle-aged adults, especially on health rating (Model 3: R² change = 0.11 for ages 18-24y, 0.14 for 45-54y, 0.27 for 75y+). Conclusions: Sleep need explains more variance in daytime function and self-rated health than sleep duration. The role of sleep need on other daytime consequences, and in clinical populations, needs further exploration.